YIELD AND BAKING PROPERTIES OF WINTER WHEAT GRAIN AT DIFFERENT DOSES AND TERMS OF NITROGEN FERTILIZER APPLICATION - Hospodarenko, G. M.; Cherno, O. D.; Lubich, V. V.; Ryabovol, Y. S.; Kryzhanivsky, V. G. (Scientific Progress & Innovations, 2020)
The study results of the effect after using different doses and terms of nitrogen fertilizers application on the yield, physical and technological quality indicators of soft winter wheat grain in the Right-Bank Forest- Steppe of Ukraine are presented. It has been established that due to additional nitrogen fertilization it is possible to increase yield by 30–54 %. After applying nitrogen fertilizers at a dose of 150 kg / ha during three terms, no significant yield increase was obtained as compared with applying nitrogen fertilizers at a dose of 120 kg/ha in tillering and leaf-tube forming phases. With increasing doses of fertilizers, covering expenditures of 1 kg active substance of fertilizers with yield growth decreased. A very strong correlation (R = 0.98) was established between thousand-kernel weight and the yield. No significant effects of doses and terms of nitrogen fertilizers’ application on grain hectoliter weight indices were found. The correlation coefficient between thousand-kernel weight and grain hectoliter weight was strong (R= 0.7). Significant increases in protein and gluten content were obtained after applying nitrogen fertilizer at a dose of N60 + N60 in tillering and leaf-tube forming phases. Approximation reliability between protein content in winter wheat grain and fertilizing intensification was high (R2 = 0.89). The indicator of gluten content stability over the years of cultivation tended to decrease at increasing doses of fertilizers. It has been found that, as to sedimentation rate, flour strength in all variants of the experiment, was average, but had a significant increase as compared with areas without fertilizers. A very strong correlation (R = 0.99) was found between protein content and sedimentation rate. Starch content tended to decrease with increasing doses of fertilizers. The inverse correlation (R = -0.94) between protein and starch content was established.